Educação e agricultura camponesa em Araras/SP: apontamentos para a educação em Ciências - Sala, Lorena Laís (Universidade Federal de São Carlos, 2023)
Rural schools have a fundamental role, which goes beyond the act of educating, is an educational modality that aims at the social and political transformation of the subjects and the various dimensions of individuals. In this perspective, science education is one of the responsible for the transformation of students into more critical citizens and capable of becoming agents of transformation of the world in which they live. Thus, this research, which has a qualitative character, sought to identify aspects of everyday peasant life that can contribute to the teaching of science. Semi-structured interviews were conducted with five family members of students from the field school, as well as observations, with a field diary. In this context, the participants of the research present the ideal school, which here we call dream school, and according to them this school constitutes as one of the fundamental tools for the continuity of rural settlements, family farming and aspects that involve life in the countryside. In addition, the data presented show the possibility of dialogue between family farming and science teaching, which is based on the social reality of students and the community, which is essential for the subjects to transform their social reality. In this sense, from the voices that have long been silenced, there are possibilities that can contribute in various aspects to this school and the return of their activities, approach to life in the field and the Operational Guidelines for Basic Education in the field.
Education and peasant agriculture in Araras/SP: notes for Science education
Keywords: Escola do campo; Ensino de Ciências; Assentamentos rurais; Rural school; Science education; Rural settlements; CIENCIAS HUMANAS::EDUCACAO